До характеристики принципів адміністративно-правового регулювання медичного обслуговування поліцейських - Смик, А. С.; Smyk, A. S. (Прикарпатський юридичний вісник. - 2019. - Вип. 1(26), т. 4. - С. 135-139, 2019)
Проаналізовано зміст та значення категорії «принцип», на основі чого виділено сутність принципів адміністративно-правового регулювання медичного обслуговування поліцейських. Окреслено доктринальні та законодавчі підходи щодо класифікації та переліку вказаних принципів. Сформовано авторську позицію про склад та видові групи принципів адміністративно-правового регулювання медичного обслуговування співробітників органів Національної поліції України.

The article analyzes the content and meaning of the category principle , based on which the essence of the principles of administrative and legal regulation of medical care for police officers. Doctrinal and legislative approaches to the classification and list of these principles are outlined. The author's position on the composition and species groups of the principles of administrative and legal regulation of medical care for employees of the National Police of Ukraine has been formed. Within the administrative and legal regulation of police care, the author identifies the following administrative and sectoral principles: the principle of hierarchy, the principles of efficiency, effectiveness and comprehensive control over the work of specialized police officers, the principle of science and innovation, the principle of legal competence. The article also considers special principles of administrative and legal regulation of medical care for police officers: the principle of integration, the principle of specification, the principle of coordination. The conclusion is made on the expediency of including in the relevant sections of the Law of Ukraine On National Police from 02.07.2015 №580-VII provisions, which will list the above principles of administrative and legal regulation of medical care for police officers.

Проанализировано содержание и значение категории «принцип», на основе чего выделена сущность принципов административно-правового регулирования медицинского обслуживания полицейских. Обозначены доктринальные и законодательные подходы по классификации и перечню указанных принципов. Сформирована авторская позиция о составе и видовых группах принципов административно-правового регулирования медицинского обслуживания сотрудников органов Национальной полиции Украины.
To characterize the principles of administrative and legal regulation of medical care for police officers
Keywords: медичне обслуговування; health care; медицинское обслуживание; поліцейські; police officers; полицейские; адміністративно-правове регулювання; administrative and legal regulation; административно-правовое регулирование; принципи; principles; принципы